1984
DOI: 10.1111/j.1526-4610.1984.hed2406339.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Thromboxane Production in Migraine Patients During Headache‐Free Period

Abstract: SYNOPSIS To study the role of the proaggregatory, vasoconstrictory thromboxane A 2 (TxA 2 ) in migraine, the plasma levels of Thromboxane B 2 (TxB 2 ), the stabile metabolite of TxA 2 , were measured from 14 adults and 8 children with migraine during the attack‐free interval. In addition, the platelets' capacity to generate TxB 2 during spontaneous clotting was studied. The plasma TxB 2 concentrations were lowered in the adult migraine patients. Also the platelets' capacity to produce TxB 2 was reduced in migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…9,25,26 A further interesting finding is the decrease in thromboxane production during the period between attacks in patients with classical migraine. 7 Our results establish the efficacy of nicardipine in migraine attacks, as corroborated by pharmacological and clinical evidence indicating the use of calcium blocking agents for the prophylaxis of classical migraine and cluster headache. 27,28 The side effects observed are similar to those in the classical prophylactic treatments of migraine.…”
Section: Discussionsupporting
confidence: 77%
“…9,25,26 A further interesting finding is the decrease in thromboxane production during the period between attacks in patients with classical migraine. 7 Our results establish the efficacy of nicardipine in migraine attacks, as corroborated by pharmacological and clinical evidence indicating the use of calcium blocking agents for the prophylaxis of classical migraine and cluster headache. 27,28 The side effects observed are similar to those in the classical prophylactic treatments of migraine.…”
Section: Discussionsupporting
confidence: 77%
“…Our results, in accordance with another study that found decreased production of plasma inflammatory mediators, might be explained in part as a result of increased consumption of arachidonic acid by the platelets during migraine attacks 19 . Arachidonic acid is metabolized either to prostanoids via the cyclooxygenase pathway or to leukotrienes via the lipoxygenase pathway.…”
Section: Commentssupporting
confidence: 92%
“…The production of TXB 2 levels has been discussed controversially. Keinanen‐Kiukaanniemi et al reported lower levels during the headache‐free period, 19 while Kitano et al demonstrated higher TXB 2 levels in migraineurs compared with healthy controls during headache‐free periods 20 . With regard to leukotrienes, several studies reported the involvement of these mediators in the pathogenesis of migraine 10,21,22 .…”
Section: Commentsmentioning
confidence: 99%